The Interrelation of Philosophy, Science, and Revealed Truth: An Epistemological Perspective - Andi Syahrul; Hamzah Harun; Andi Aderus (Journal AGENCY, 2025)
Purpose – This study aims to explore the epistemological integration among philosophy, science, and revelation as three essential frameworks in the pursuit of truth and knowledge. Design/methodology/approach – This research applies a qualitative approach with a philosophical-hermeneutical method. It involves descriptive and comparative analysis of primary and secondary sources from classical and contemporary scholars, incorporating Islamic theological discourse, scientific theory, and philosophical reasoning. Findings – The study finds that philosophy provides the rational foundation, science offers empirical evidence, and revelation delivers transcendental truth. The interaction of these three constructs reveals both convergence and tension, yet they are not mutually exclusive. Instead, when integrated, they present a holistic epistemology that supports a comprehensive worldview—balancing reason, observation, and faith. Originality/value – This paper contributes to the discourse on Islamic epistemology by proposing a triadic framework of knowledge that bridges the gap between reason and faith in contemporary knowledge production.